Inclusive assessment practices and their application in the inclusion of students with visual impairment in higher education in Tanzania - Lawi , Chiza; Muzata, Kenneth Kapalu (Eureka: Journal of Educational Research, 2025)
The agenda for inclusive education cannot be fully realised if inclusive assessment is ignored by education systems and its practitioners. This was a qualitative study that investigated the inclusive assessment practices employed for Students with Visual Impairment (SwVI) in one selected Tanzanian higher education institution. Using an intrinsic case study design, the study answered two main research questions on what assessment practices were used when assessing SwVI and how the assessment practices were applied. Twenty participants (20) were purposively sampled to participate in interviews, and focus group discussions. Thematic analysis was used to make sense of the data. The findings revealed that there was adequate effort made by the higher education institution under study to use a variety of assessment methods to meet the needs of SwVI. Despite these efforts, students encountered a number of challenges in the application of some assessment practices. Among the main challenges was the failure of some students to read braille grade 2 and the lack of skills to use technological devices such as computers in assessment, even though computers were available. The university management should organise training programmes for SwVI in braille grade 2 and on how to use computers in assessment.